2013
DOI: 10.1103/physrevd.87.034041
|View full text |Cite
|
Sign up to set email alerts
|

Spinning the top quark

Abstract: We propose to measure the threshold lepton asymmetry, that is the forward-backward asymmetry of the charged lepton in tt events near the production threshold. At threshold top quark pairs are produced in an s-wave. Angular momentum conservation then implies that the top spins equal the spin of the initial state which -in the case of quarks -is uniquely fixed by the chirality of the initial quarks. Thus measuring final state top spins determines the chirality of the quarks which produced them. Information about… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…1. In [60][61][62][63][64][65][66][67][68][69][70][71], comparisons between different models are carried out, and study of those models or measurements in the LHC context can be found in [72][73][74][75][76][77][78][79][80][81][82][83][84].…”
Section: Introductionmentioning
confidence: 99%
“…1. In [60][61][62][63][64][65][66][67][68][69][70][71], comparisons between different models are carried out, and study of those models or measurements in the LHC context can be found in [72][73][74][75][76][77][78][79][80][81][82][83][84].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that neither the Tevatron nor the Large Hadron Collider (LHC) have observed any other anomaly in top or jet physics sets strong constraints on possible explanations in terms of new physics [3][4][5]. One of the few surviving explanations, compatible with the present measurements of the tt invariant mass spectrum [6] and the charge asymmetry at the LHC [7, 8], is a relatively light colour octet vector boson (called here 'gluon' for brevity) with mass M 1 TeV and with suppressed axial-vector couplings to the light quarks and sizeable axial-vector couplings to top quarks [9][10][11][12][13][14][15][16][17]. The axial coupling ensures cancelation of the interference terms between the SM and new physics contribution [18][19][20] in symmetric observables while preserving the contribution to the asymmetry.…”
mentioning
confidence: 83%
“…In particular, the lepton-based asymmetry near the tt threshold directly probes the chiralities of the initial qq pair [126]. Since NP A FB contributions here originate from RH up quark/antiquark collisions, a negative contribution to the leptonbased asymmetry is expected near threshold.…”
Section: Bottom and Lepton-based Top A Fb At The Tevatronmentioning
confidence: 99%
“…The forward-backward charged lepton (or lepton-based) asymmetry in tt production at the Tevatron is a useful discriminant in order to better characterize the NP source explaining the top A FB [124][125][126][127][128][129]. In particular, the lepton-based asymmetry near the tt threshold directly probes the chiralities of the initial qq pair [126].…”
Section: Bottom and Lepton-based Top A Fb At The Tevatronmentioning
confidence: 99%